Business security architecture - SONIUK Ольга (Ius Modernum, 2024)
Protection of business from todayʼs military challenges, post-war recovery of Ukraine and integration into the European space guides researchers to develop a set of business security measures. The evolution of approaches in the study of the security of business activity has gone from the micro-level of national economic security to integrated risk management in corporate management according to international standards. The recommendations of representtatives of various fields of knowledge require the agreement of basic terminology, the systematization of the main elements of business security into a common architecture, and the regulation of the specified process by a special legislative act. The hypothesis of the study is to confirm the expediency of considering business security as a complex architecture, characterized by the multifaceted interrelationships and mutual influence of constituent elements both within the system and with the external environment. State regulation of the business environment should not only stimulate the development of a certain sphere of the national economy (subject-object influence), but also recognize the subjectivity of entrepreneurs (state-enterprise interaction), the priority of the interests of the latter, expanding freedom and guarantees of protection for business. The purpose of the article is to reveal the architecture of business security, to substantiate the complexity of the interrelationships of elements, and the complexity of the development of enterprise security measures. The article proposes the authorʼs matrix of enterprise security at the tactical (up to 1 year) level and the generalized scheme of the business security architecture at the strategic level of the organization of business activities.